METHODS OF IMROVING THE STUDENT’S PERSONAL COMPETENCE THROGH EDUCATIONL TECHNOLOGIES - B.B.Umirov (Scholar Express Journal, 2022)
In this article, the training of informatics teachers is considered as a module in the process of integrating pedagogical and information-communication technologies
Keywords: package of practical applications; text editors; individual